2022
DOI: 10.1007/s13346-021-01103-4
|View full text |Cite
|
Sign up to set email alerts
|

Critical parameters for design and development of multivalent nanoconstructs: recent trends

Abstract: Graphical abstract A century ago, the groundbreaking concept of the magic bullet was given by Paul Ehrlich. Since then, this concept has been extensively explored in various forms to date. The concept of multivalency is among such advancements of the magic bullet concept. Biologically, the concept of multivalency plays a critical role in significantly huge numbers of biochemical interactions. This concept is the sole reason behind the higher affinity of biological molecules like viruses to more sele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 157 publications
(179 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, from the molecular level, IMI or nano-IMI distributes to different parts of the body upon entering the organisms, whereas only the fraction of binding to the toxic target site (i.e., toxicologically available concentration) actually causes toxicity . Chemical forms substantially influence the binding affinity of the chemical to the target site. , A previous study demonstrated that nanomaterials, graphene oxide, can strongly bind to receptor proteins through multiple noncovalent interactions, as suggested by molecular modeling . With the slower elimination rate of nano-IMI compared to IMI in zebrafish embryos, it is also likely that nano-IMI could exhibit a stronger binding affinity to nAChR compared to IMI due to distinct molecular interactions, supported by the significantly slower elimination rate of nano-IMI.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, from the molecular level, IMI or nano-IMI distributes to different parts of the body upon entering the organisms, whereas only the fraction of binding to the toxic target site (i.e., toxicologically available concentration) actually causes toxicity . Chemical forms substantially influence the binding affinity of the chemical to the target site. , A previous study demonstrated that nanomaterials, graphene oxide, can strongly bind to receptor proteins through multiple noncovalent interactions, as suggested by molecular modeling . With the slower elimination rate of nano-IMI compared to IMI in zebrafish embryos, it is also likely that nano-IMI could exhibit a stronger binding affinity to nAChR compared to IMI due to distinct molecular interactions, supported by the significantly slower elimination rate of nano-IMI.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies reported in literature highlight that multiple targeting ligands on nanoparticle surface can increase binding avidity, accelerate the internalization process and, thus, can be considered to enhance the therapeutic efficacy of a drug nanocarrier [ 45 , 46 , 47 ]. In order to investigate the effect of the targeting agent density on nanoparticle surface on targeting profile of the nanosystems, a library of Rho-FA x- AuNPs was produced at increasing density of FA-PEG 3.5kDa -SH followed by gold surface saturation with Rho-PEG 2kDa -SH.…”
Section: Resultsmentioning
confidence: 99%
“…Key features include multivalency and ligand density, which can increase the overall binding avidity of the nanoparticle, and non‐obvious parameters such as the linker between the membrane and the binding domain, nanoparticle composition, and ligand fluidity can also affect specificty of binding and uptake. [ 39,40 ] Studies have shown that tuning both the affinity of the ligand and the valency of the nanoparticle affects binding to high, medium, and low target‐expressing cells. [ 26 ] Here, we demonstrate differences in binding between monovalent, soluble proteins and multivalent nanoparticles (Figure 2, and Figure S7, Supporting Information).…”
Section: Discussionmentioning
confidence: 99%